How Does Inequality Affect the Residents’ Subjective Well-Being: Inequality of Opportunity and Inequality of Effort - He, Qizhi; Tong, Hao; Liu, Jia-Bao (Frontiers in Psychology, 2022)
Based on the Chinese General Social Survey database (2010-2015), this paper explores the relationship between income inequality and residents’ subjective well-being from the perspective of inequality of opportunity and inequality of effort. We find that inequality of opportunity has a negative effects on subjective well-being in China, where inequality of effort has a positive effects. Our empirical results are robust for changing the inequality indicators. In the sub-sample studies, consistent conclusions are obtained in rural areas, whereas in urban areas only inequality of effort has a significant impact. The results of mechanism study shows that inequality of opportunity decreases residents’ sense of fairness, and inequality of effort increases residents’ sense of fairness, thus affecting their subjective well-being. The results of this study provide a good response to the inconclusive research findings on the impact of income inequality on subjective well-being.